P448 Oral beclomethasone dipropionate as an add-on therapy and response prediction in Korean patients with ulcerative colitis. (21st January 2022) - Kim, K; Hong, H S; Oh, K; Lee, J Y; Hong, S W; Park, J H; Hwang, S W; Yang, D H; Byeon, J S; Ye, B D; Myung, S J; Yang, S K; et al.
Abstract: Background: We aimed to investigate the efficacy of oral beclomethasone dipropionate (BDP) as an add-on therapy to concomitant drugs and to clarify the predictive factors for response to oral BDP in Korean patients with ulcerative colitis (UC). Methods: Patients with a stable concomitant drug regimen with exposure to oral BDP (5 mg/day) within 30 days before initiation were included. The partial Mayo score (pMS) was used to evaluate response to oral BDP. Clinical remission (CREM) was defined as a posttreatment pMS ≤1 point. Clinical response (CRES) was defined as an at least 2-points decrease in the posttreatment pMS and an at least 30% decrease from the baseline pMS. Patients without CREM or CRES were considered nonresponders (NRs). Results: Of total 100 patients, 37 showed CREM, 19 showed CRES, and 44 were NRs (Table 1). The CREM group included more patients with mild disease activity (75.7% vs. 43.2%, P =0.011) than the NR group. In contrast to NR group, responders including CREM and CRES showed significant improvement of posttreatment ESR and CRP (ESR with P =0.001, CRP with P =0.004, respectively). Moreover, initial rectal bleeding subscore (RBS) was significantly different between CREM and CRES, or NR (both with P <0.001). In multivariate logistic regression analysis, initially mild disease activity was the only predictive factor for CREM (odds ratio, 3.580; 95% confidence interval, 1.342–9.548) (Table 2). Conclusion: Oral BDP is efficacious as an add-on therapy in Korean UC patients. In case of acute aggravation, patients with mild disease activity, especially low RBS, may be good candidates for oral BDP.